A natural WNT signaling variant potently synergizes with Cdkn2ab loss in skin carcinogenesis - Paul Krimpenfort (Nature Portfolio, 2019)
Cdkn2ab knockout mice develop skin tumours but this phenotype is lost on backcrossing of the mice. Here, the authors describe a genetic variant encompassing Wnt7b that synergises with Cdkn2ab loss and is required for tumour formation in these mice.